2016
DOI: 10.1039/c5an02062j
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering biologically significant lipid isomers with liquid chromatography, ion mobility spectrometry and mass spectrometry

Abstract: Understanding how biological molecules are generated, metabolized and eliminated in living systems is important for interpreting processes such as immune response and disease pathology. While genomic and proteomic studies have provided vast amounts of information over the last several decades, interest in lipidomics has also grown due to improved analytical technologies revealing altered lipid metabolism in type 2 diabetes, cancer, and lipid storage disease. Mass spectrometry (MS) measurements are currently th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
211
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(232 citation statements)
references
References 42 publications
20
211
0
1
Order By: Relevance
“…IM can also resolve additional lipid classes within each group on the basis of their different headgroups. There is strong consensus between the literature and our results that PCs have larger gas-phase conformations than other phospholipids (49,50). Within the PEs, we observe a clear separation between PEs with two ester linkages and PEs with one vinyl ether linkage (plasmalogen PEs, PEp), with the plasmalogen PEs having slightly larger CCS values than PEs with the same fatty acid compositions in positive mode (supplemental Table S1) and slightly smaller CCS values in negative mode (supplemental Table S2).…”
Section: Untargeted Lipidomics By Hilic-im-msmentioning
confidence: 69%
See 2 more Smart Citations
“…IM can also resolve additional lipid classes within each group on the basis of their different headgroups. There is strong consensus between the literature and our results that PCs have larger gas-phase conformations than other phospholipids (49,50). Within the PEs, we observe a clear separation between PEs with two ester linkages and PEs with one vinyl ether linkage (plasmalogen PEs, PEp), with the plasmalogen PEs having slightly larger CCS values than PEs with the same fatty acid compositions in positive mode (supplemental Table S1) and slightly smaller CCS values in negative mode (supplemental Table S2).…”
Section: Untargeted Lipidomics By Hilic-im-msmentioning
confidence: 69%
“…However, the positional isomers were not differentiated in this work. Previous work by Baker and coworkers (49) reported that positional isomers of phospholipids could be differentiated by IM separation, but the difference between the drift times of each pair of isomers is less than 1%, which is beyond the resolution of our instrument. In another study by Groessl et al (52), the effect of E/Z isomers on the CCS of PC(18:1/18:1) was also found to be less than 0.5%.…”
Section: Ccs Measurements Of Lipids By Twim-ms Calibrationmentioning
confidence: 93%
See 1 more Smart Citation
“…30 Coupling LC with ion-mobility has shown potential for facilitating multi-dimensional LC-IMS-MS measurements, permitting isomeric lipids within complex biological extract to be resolved. 31 Despite these significant advances in lipid isomer separation and analysis, these techniques do not consistently allow isomer identification (e.g. the determination of the location of double bonds, stereochemistry about the double bonds, or sn -positions) without requiring analysis of an exhaustive number of standards which may not be commercially or synthetically available.…”
Section: Introductionmentioning
confidence: 99%
“…This method was originally developed for total lipid extractions 9,11 and more recently was amended for the simultaneous extraction of metabolites, proteins, and lipids from a single sample 12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30, enabling less sample quantity and experimental variability 10 . In the MPLEx protocol, chloroform is not miscible with water, which provides the basis for the triphasic chemical separation of sample constituents into distinct fractions.…”
Section: Introductionmentioning
confidence: 99%